Wear and frictional performance of polymeric composites aged in various solutions - Yousif, B.F.; Nirmal, Umar (2011)
The aim of the present work is to investigate the effect of aging process on the wear and frictional characteristics of polyester composites based on oil palm fibres. Prepared samples of treated oil palm fibre reinforced polyester (T-OPRP) composite were immersed in different types of solutions (i.e. water, salt water, diesel, petrol and engine oil) for three years. The samples were then tested on a Pin on disc (POD) machine subjected to a polished stainless steel counterface under dry adhesive wear at different sliding distances (0-6.72 km). Scanning electron microscopy (SEM) was used to observe the damage features on the worn surfaces. Results revealed that aging process has pronounced influence on the adhesive wear and frictional behaviour of the T-OPRP composite. Immersing the samples in water and salt water demonstrated poorest wear performance as compared to the ones immersed in engine oil and diesel. This was mainly due to the higher viscosities of engine oil and diesel solutions as compared to the rest. (C) 2011 Elsevier B.V. All rights reserved.